Alternative Therapies for the Prevention of Postoperative Nausea and Vomiting - Stoicea, Nicoleta; Gan, Tong J.; Joseph, Nicholas; Uribe, Alberto; Pandya, Jyoti; Dalal, Rohan; Bergese, Sergio D. (Frontiers in Medicine, 2015)
Post-operative nausea and vomiting (PONV) is a complication affecting between 20% and 40% of all surgery patients, with high-risk patients experiencing rates of up to 80%. Recent studies and publications have shed light on the uses of alternative treatment for PONV, through their modulation of endogenous opioid neuropeptides and neurokinin ligands. In addition to reducing PONV, hypnosis was reported to be useful in attenuating postoperative pain, anxiety, and contributing to hemodynamic stability. Music therapy has been utilized to deepen the sedation level and decrease patient anxiety, antiemetic and analgesic requirements, hospital length of stay, and fatigue. Isopropyl alcohol and peppermint oil aromatherapy have both been used to reduce postoperative nausea. With correct training in traditional Chinese healing techniques, acupuncture (APu) at the P6 acupoint has also been shown to be useful in preventing early PONV, post-discharge nausea and vomiting, and alleviating of pain. Electro-acupuncture (EAPu), as with APu, provided analgesic and antiemetic effects through release of opioid neuropeptides and modulation. These non-pharmacological modalities of treatment contribute to an overall patient wellbeing, assisting in physical and emotional healing.